Inhibitory effect of Monascus purpureus pigment extracts against fungi and mechanism of action - Majhi, Swapna; Dhale, Mohan Appasaheb; Honganoor Puttananjaiah, Mohankumari (Frontiers in Sustainable Food Systems, 2023)
The fungus Monascus produces several secondary metabolites of different pigment hues. These pigments have shown various biological activities. Herein, Monascus purpureus pigment extracts were tested (in-vitro) against Penicillium expansum MTCC 4900, Rhizopus stolinfer MTCC 10595, and Aspergillus niger MTCC 8652 for antifungal activity. The UV-visible spectrum of M. purpureus fermented rice extracts showed λmax at 395, 425 and 500nm. This indicated the solubility of yellow, orange and red pigment in polar based solvent extraction. The M. purpureus pigment extracts inhibited the radial growth and conidial germination of the test fungi. The fungi treated with pigment extract stained with DiBAC (a vital stain) emitted green fluorescence under fluorescent microscopic. These results indicated pigment extracts have affected membrane potential of the treated fungi. Hence, the fungicidal activity of the pigment extracts is due to the disruption of cell membrane. The HPLC analysis of the pigment revealed the presence of two major peaks. The UV-visible spectrum corresponding to the HPLC peak at 12 minute retention time revealed the presence of orange pigment rubropunctatin. Apparently, the rubropunctatin present in the extracts exhibited fungicidal activity. Further studies are warranted to assess the applications of M. purpureus pigments in preventing and treating fungi-related diseases.